Influence of Chitosan Oligosaccharide on the Growth Performance of Broilers under the Libyan Western Mountain Climate - د. الهـادي جلبــان (African Journal of Advanced Pure and Applied Sciences, 2025)
This study was conducted to investigate The effect of adding chitosan oligosaccharide (C6H11NO4)n on broiler’s growth performance during the climate of the western mountain region in Libya, where a lot of farmers rearing broilers, and almost all families consume broiler meat every day. Three levels of chitosan oligosaccharides, 0 mg/kg (control treatment), 100mg chitosan / kg diet (treatment 1) and 200mg chitosan /kg diet (treatment 2) were added to the checks diet. Chitosan is an oligosaccharide used lately as antioxidant, antimicrobial and to improve birds performance, meat and eggs quietly. Chitosan was added to the basal corn-soybean diet. 120 Cobb strain checks, one – day old, were reared in open pen and randomly distributed to 3 treatments, 40 checks for each treatment , 10 checks for each replicate. The experiment continued for 6 weeks. Food and water were available for birds ad-libtum, light period is 24h/per day, temperature was recorded daily, usual fans on the walls were used for ventilation, vaccination and other treatments were done on time. Body weight, food consumption and food conversion ratio were calculated weekly, and the means were recorded. The results showed that adding of chitosan 200mg significantly (P<0.05) improved the body weight in the T2 birds, compared with the control group, while feed intake and feed conversion ratio (FCR) did not differ significantly between control group and the two chitosan groups. From these results it could be say adding chitosan can improve broiler performance in this region instead of undesired usual growth promoters.